Politeness Strategies in Context Use Represents in “A Dog’s Journey Movie” - Wirantini, Ni Made (STKIP AGAMA HINDU SINGARAJA, 2024)
The purpose of this study is to identify the politeness strategies in context used by the characters in A Dog’s Journey Movie Manuscript. This investigation is qualitative research. The information is spoken words that show the characters' employment of politeness strategies. The manuscript and its movie serve as the data sources. The researcher employed documentation and observation techniques to gather the data. The data are analyzed using the data from Brown and Levinson (1987). According to the study's findings, the characters use three different kinds of politeness techniques: bald on record (15%), positive politeness (22%), and negative politeness (10% percent). Of all the politeness methods employed by the characters in this film, the positive politeness strategy eventually become the most frequently shows. The use of language in this film is adjusted and influenced by the closeness of their relationship as well as by different social contexts.